PENJADWALAN ALOKASI JOB BERBASIS METODA HEURISTIK PADA LINGKUNGAN GRID INDONESIAN EDUCATION GRID - I Nyoman Rudy Hendrawan; Waskitho Wibisono (Jurnal Ilmu Komputer, 2013)
Scheduling mechanism on a grid system became one of important factor in measuring performance of thegrid system. Moreover, building a grid system which is used for experiment or research is time and cost consuming,and then a grid system simulation can be an alternative. In a previous study has been conducted by designing andsimulating of the grid system which is called Indonesian Education Grid (IndoEdu-Grid). A random allocation jobscheduling method was used in the previous study (the method is called UD-IndoEdu-Grid in the next section).Therefore, in this paper we proposed an allocation job scheduling based on heuristic method called TS-IndoEdu-Grid, and thus expected to improve the performance of the IndoEdu-Grid environment. Experiment results show thatby using the TS-IndoEdu-Grid method could reduce makespan by 20% to UD-IndoEdu-Grid. In flowtime parameterthe TS-IndoEdu-Grid method also produces 94% smaller than the UD-IndoEdu-Grid method